(untitled) (Bangladesh Agronomy Journal, 2016)
A field experiment was conducted at the Agronomy field, Sher-e-Bangla Agricultural University, Dhaka from November 2012 to July 2013. Experiment consisted of two factors, viz. (i) variety- BRRI dhan29 (V1) and BRRI hybrid dhan2 (V2), and (ii) planting materials- nursery seedlings (N), first generation clonal tillers (C1) collected from N, second generation clonal tillers (C2) collected from C1, third generation clonal tillers (C3) collected from C2 and fourth generation clonal tillers (C4) collected from C3, following split-plot design with three replications. Results revealed that despite higher (161.29) number of filled grains as obtained from BRRI dhan29 while lower (139.31) from BRRI hybrid dhan2, and maximum weight of 1000-grains (26.50 g) from hybrid variety and the minimum from the inbred one (19.70 g), the grain yield was not varied significantly. Among the planting materials nursery seedlings gave the maximum (9.23 t ha-1) grain yield that followed by first generation clonal tillers (7.44 t ha-1), and second generation clonal tillers (6.57 t ha-1). The third and fourth generation clonal tillers also produced around 3 t ha-1 grain yield. The maximum grain yield (9.6 t ha-1) was observed from the combination of nursery seedlings with BRRI hybrid dhan2 which is statistically similar to the combination of same planting material with BRRI dhan29 (8.86 t ha-1). The first and second generation clonal tillers of both the varieties produced more than 6.0 t ha-1 grain yield. Therefore, clonal tillers can be used as planting materials for both hybrid and inbred rice cultivation in case of scarce supply of nursery seedlings. Bangladesh Agron. J. 2016, 19(1): 59-66